Using information literacy to support teaching practicum students. Issue 2 (12th June 2017) - Whitver, Sara Maurice
Abstract : Purpose: Library literature is filled with studies that lament the challenges of the faculty–librarian relationship. While many examples of productive collaborations can be found in recent literature, librarians still find it challenging on the local level to reshape old perceptions of the role of the librarian. This purpose of this paper is to suggest that by building relationships with graduate student teachers during their first semester of teaching, many of those challenges can be reversed. Design/methodology/approach: The author describes her work with a writing program teaching practicum, a 1-h course for graduate students in the department of English who are engaged in teaching for the first time. Findings: This paper offers a model for building collaborative relationships with graduate students who are first-time teachers of writing to support the development of information literacy in their teaching practices. Using the community-building principles of Writing Across the Disciplines and the collaboration initiatives referenced in writing program literature, librarians can establish peer relationships with first-time teachers, which can have long-lasting effects on faculty–librarian relationships, as those teachers continue to teach throughout their career. Originality/value: Many articles exist that talk about faculty–librarian collaborations, but virtually none have explored the role of librarian collaborations with first-time teachers or, by extension, with graduate student teachers in general. This paper offers one model for establishing a productive role for the librarian within first-year writing courses while also empowering first-time teachers to successfully design and implement researched writing assignments.